Exploring how substance use impedes engagement along the HIV care continuum: A qualitative exploration - Marya eGwadz; Marya eGwadz; Rebecca ede Guzman; Robert eFreeman; Alexandra eKutnick; Elizabeth eSilverman; Noelle Regina Leonard; Noelle Regina Leonard; Amanda Spring Ritchie; Corrine eMunoz-Plaza; Nadim eSalomon; Hannah eWolfe; et al. (Frontiers Media S.A., 2016)
Drug use is associated with low uptake of HIV antiretroviral therapy (ART), an under-studied step in the HIV care continuum, and insufficient engagement in HIV primary care. However, the specific underlying mechanisms by which drug use impedes these HIV health outcomes are poorly understood. The present qualitative study addresses this gap in the literature, focusing on African American/Black and Hispanic persons living with HIV (PLWH) who had delayed, declined, or discontinued ART and who also were generally poorly engaged in health care. Participants (N=37) were purposively sampled from a larger study for maximum variation on HIV indices. They engaged in 1-2 hour audio-recorded in-depth semi-structured interviews on HIV histories guided by a multi-level social cognitive theory. Transcripts were analyzed using a systematic content analysis approach. Consistent with the existing literature, heavy substance use, but not casual or social use, impeded ART uptake, mainly by undermining confidence in medication management abilities and triggering depression. The confluence of African American/Black or Latino race/ethnicity, poverty, and drug use was associated with high levels of perceived stigma and inferior treatment in health care settings compared to their peers. Further, providers were described as frequently assuming participants were selling their medications to buy drugs, which strained provider-patient relationships. High levels of medical distrust, common in this population, created fears of ART and of negative interactions between street drugs and ART, but participants could not easily discuss this concern with health care providers. Barriers to ART initiation and HIV care were embedded in other structural- and social-level challenges, which disproportionately affect low-income African American/Black and Hispanic PLWH (e.g. homelessness, violence). Yet, HIV management was cyclical. In collaboration with trusted providers and ancillary staff, participants commonly reduced substance use and initiated or re-initiated ART. The present study highlights a number of addressable barriers to ART initiation and engagement in HIV care for this vulnerable population, as well as gaps in current practice and potential junctures for intervention efforts.